Prospects of using secondary energy resources - Sokolenko, Anatoly; Shevchenko, Oleksandr; Vasylkivskyi, Kostyantyn; Stepanets, Oleg; Vinnichenko, Inna (My University, 2019)
The paper deals with the peculiarities of thermodynamic analysis of technological systems of food production with generation of secondary steam. System analysis is based on information about production, equipment operation, modern scientific achievements and modeling methods in chemical, physical, mathematical and other sciences. The information about applied energy and thermodynamic criteria, criteria of optimization of systems, list of sequence of actions on improvement of systems is given. Secondary energy resources of food industries are often represented by thermal energy of liquid media or secondary steam. Regeneration of the secondary steam allows, during its subsequent condensation, to return the heat potential of the steam to the media. This means that in the systems where the increase in the thermodynamic parameters of steam due to its compression, there is the use of Carno's return cycle. Such use occurs both in closed and open cycles. The description of the physical processes accompanying the work of the thermocompressors is subject to mathematical modeling based on the laws of conservation of energy, mass conservation and conservation of impulses. The assessment of the suitability for using secondary energy resources is based on exergy methods in order to determine the directions for their further improvement. For identical pressures in the mixing chamber, the efficiency of the actual compressor is higher than the ratio of the ejection coefficients of the real and ideal compressors, since internal irreversible losses along with the reduction of the ejection rate result in the increase of the specific exergy of the compressed flow.
Keywords: thermodynamics; recuperation; secondary energy resources; secondary steam; enthalpy; exergy; кафедра мехатроніки та пакувальної техніки; кафедра процесів і апаратів харчових виробництв